1977
DOI: 10.1104/pp.60.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Photosynthetic Rhythms in Marine Dinoflagellates

Abstract: Using data from light-dark cultures of Gonyaulaxpolyedra entrained to a 24-hour cyde, whole ceUi absorption curves and photosynthesishrradiance curves were constructed for various circadian times. While whole celi absorbance and half-satuntion constants of photosynthesis showed no statisticd difference that could be directly related to the photosynthetic rhythm, the initid slope of the photosynthesis-irradiance curve was a time-dependent parameter which altered in direct proportion to the change in photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…High measurements of α B have also been observed in other studies , Malone & Neale 1981, Kelly & Doering 1997 contrasts with that reported in diel (MacCaull & Platt 1977, Prézelin & Sweeney 1977, daily (Cote & Platt 1983) and seasonal ) P-I studies, where range factors of α B were similar to or less than P B m . In those studies, however, P-I parameters did not necessarily correlate temporally, as was observed in the present study.…”
Section: Mid and Bottom Waterscontrasting
confidence: 51%
“…High measurements of α B have also been observed in other studies , Malone & Neale 1981, Kelly & Doering 1997 contrasts with that reported in diel (MacCaull & Platt 1977, Prézelin & Sweeney 1977, daily (Cote & Platt 1983) and seasonal ) P-I studies, where range factors of α B were similar to or less than P B m . In those studies, however, P-I parameters did not necessarily correlate temporally, as was observed in the present study.…”
Section: Mid and Bottom Waterscontrasting
confidence: 51%
“…The perpetuation of the weak circadian cycle observed in situ under constant conditions was proof of an endogenous control of the photosynthetic response of the microalgae (Prezelin & Sweeney 1977). Thus, during neap tide, when the stress of semidiurnal exposure is absent, the circadian variations in the photosynthetic response of epilithic microalgae are, at least in part, regulated by endogenous phasing.…”
Section: Endogenous Versus Exogenous Control Of Photosynthetic Responsementioning
confidence: 93%
“…The other light input pathway responds both to red and blue light, possibly sharing pigments with the photosynthesis machinery. Pharmacological inhibition of photosynthesis affects the Gonyaulax circadian system (Johnson and Hastings 1989;Roenneberg 1994), and photosynthesis is itself an output of the clock (Prezelin and Sweeney 1977;Sweeney 1986). Thus, it represents a metabolic feedback loop.…”
Section: Feedbacks Over Feedbacksmentioning
confidence: 99%